2011
DOI: 10.1089/acm.2010.0566
|View full text |Cite
|
Sign up to set email alerts
|

The Quantification of Placebo Effects Within a General Model of Health Care Outcomes

Abstract: Objectives: The objective of this study was to test a model of placebo effects in the context of a general model of health care outcomes. Design: The design of this study was a multisite, double-blind, placebo-controlled crossover trial. Settings: The study was conducted at The University of Washington Hospital, Seattle, Washington, Cooper Hospital/University Medical Center, Camden, New Jersey, and at the Neurology Center of Fairfax, Fairfax, Virginia. Subjects: One hundred and seventeen (117) patients diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In general, the exemplar accounts illustrate the synergy of positive expectancy and self-regulation capacities, factors associated with placebo responding and positive healthcare outcomes. 41 …”
Section: Discussionmentioning
confidence: 99%
“…In general, the exemplar accounts illustrate the synergy of positive expectancy and self-regulation capacities, factors associated with placebo responding and positive healthcare outcomes. 41 …”
Section: Discussionmentioning
confidence: 99%
“…The differences in the level of suggestibility between the previous and current study may be due to selection of participants (psychology students vs. students in general), recruitment procedure (SSS preformed prior to enrollment in study vs. SSS performed after consent to participate in a pharmacological study) and cultural and individual variance in the context and the performance of the test. A previous sham-controlled trial studied the effect of a pulsing electromagnetic generator on the quality of life in patients with multiple sclerosis and found that those responding to the sham treatment scored higher on absorption than non-placebo responders [27]. The study investigated placebo responses which differ from placebo effects since they also include factors such as fluctuations of symptoms and regression phenomena [3].…”
Section: Discussionmentioning
confidence: 99%
“…At the data collection session at the conclusion of course of intervention, the participant will be asked to indicate which intervention (active or placebo) they thought they had received during the last 4 weeks and to give a confidence rating on a scale of 0–10 (with 0=‘not at all confident’ and 10 = ‘extremely confident’ [55]). Global perceived effect will also be measured using a self-assessment of improvement on a seven point rating scale (1 = completely recovered, 2 = much improved, 3 = slightly improved, 4 = not changed, 5 = slightly worsened, 6 = much worsened, 7 = worse than ever) in response to the question ‘How would you rate the course of your ankle complaints since the start of this study?’ [56, 57].…”
Section: Methodsmentioning
confidence: 99%